Use of WhatsApp Group as Learning Media in Higher Education During the Covid-19 Pandemic - Agus Susilo; Andriana Sofiarini (research, training and philanthropy institution Natural Aceh, 2021)
education in the current Covid-19 pandemic era must be shifted from face-to-face learning systems to distance learning. This online learning requires suitable and appropriate media without reducing the quality of learning. The purpose of this research is the use of WhatsApp Group as a learning medium in universities during the Covid-19 pandemic. The research method used is quantitative research methods. The instrument in this quantitative research is a research questionnaire. To find out the number of research results, it is known by knowing the percentage. The impact of the Covid-19 pandemic on education, namely the existence of Covid-19, has changed the education system in Indonesia from various levels. Online learning was carried out after the ban on face-to-face learning during the Covid-19 pandemic. Online learning is carried out by utilizing online media that is relevant to needs. WhatsApp Group as a learning media in Higher Education, which is an online media commonly used in the communication process during a pandemic, was chosen to be used as a medium to support the distance learning system. WhatsApp Group apart from having powerful features, is also easy to reach and cheap in terms of data packages used for distance learning. WhatsApp Group media is a recommendation in the implementation of online learning today. The conclusion is that in the current pandemic era, online distance learning systems must use appropriate and comfortable online media without reducing their quality. WhatsApp is an online learning solution during the pandemic.